Footwear business of village owned enterprises (BUMDes) and its role in increasing rural economic activities - Ulul Hidayah; Sri Mulatsih; Yeti Lis Purnamadewi (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2020)
The village owned enterprises (BUMDes) has an important role in stimulating rural development and therefore it is necessary to examine its feasibility as a profitable business venture and has a sustainable impact on village development.  The purpose of this research is to conduct a feasibility analysis of the BUMDes and its role in developing rural economic activity.  This research method used a financial feasibility analysis to BUMDes of Harapan Jaya in Bogor Regency, Indonesia. Data were obtained through focus group discussion with informants who work in BUMDes as operational manager, supervisors, commissioners, as well as village officials and MSME entrepreneurs. The results showed that business feasibility analysis in the footwear marketing business by BUMDes is feasible as indicated by the net present value of 318 million rupiah; benefit-cost ratio 1.026; internal rate of return 35%; and a 2.56 year of payback period. Furthermore, BUMDes contributes significant profits for village. BUMDes involvement in the marketing of footwear products lead entrepreneurs and footwear workers earns a more income  than the regional minimum wage. The collaboration between BUMDes and MSME resulted in a business profit of 80 million rupiah. BUMdes governance requires an increase in the quality of human resources and organization mechanism to be more competence and productive supporting performance targets, incentive mechanisms, and job satisfaction.JEL Classification:  L32, L60, R20